ANALISIS DIFUSI LARUTAN PUPUK MELALUI DINDING MORTAR ARANG SEKAM PADI - Dian Fajar Lestari; Ahmad Tusi; Muhamad Zen Kadir (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2016)
The aim of this reasearch is to determine difussion coefficient of nutrient solution through rice husk charcoalmortar walls. This research used completely randomized design (CR) with factorial arrngement which consistedof factors. The first factor, the material composition ratios of mortars (cement : sand : rice husk charcoal),consisted of two levels: P 1 (1:3:3) and P 2 (1:3:4). The second factor, the concentration of nutrient consisted ofree levels, namely K 1 (3 mS/cm), K 2 (6 mS/cm), and K 3 (9 mS/cm). Data set was analyzed by using ANOVA,then followed by using LSD at 5% significant level. Anova showed that there was interaction between mortarmaterial composition and nutrient concentration. The best diffusion coefficient was found in the treatment P 2 K 1and P 2 K 2 (1:3:4 and the nutrient concentrations 3 mS/cm, 6 mS/cm). Nutrient solution in the treatments couldpass through the walls of mortar very well, so that it could be used as a means of fertigation.Keywords: Fertigation, Diffusion, Nutrient Solution, and Rice Husk Charcoal Mortar.